The Islamic Worldview and Language Proclivity: The Case of Modern Brunei - Sharbawi, Salbrina (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
Brunei is undergoing a language transition, with younger generations favoring English over Malay, raising concerns about the potential impact on the Islamic worldview traditionally tied to Malay. This study examines the relationship between language preference and the Islamic worldview among 67 young female Bruneian Muslims, using an online survey to assess their language use, religious identity, and perspectives on Islamic and Western ideologies. Findings reveal strong alignment with Islamic beliefs on divine matters but ambivalence on contemporary social issues like gender and dating, particularly among English-preferring participants. While a weak association between English proclivity and a Western worldview was observed, it was not statistically significant. This study highlights the complexities of language and religious identity in a globalized context, emphasizing the need for further research and adaptive strategies in Islamic education to address linguistic and ideological shifts.